O viver e o produzir a partir da formação além da técnica: o caso dos egressos da Casa Familiar Rural Santo Agostinho/Quilombo, SC, no período de 1990 a 1997 - Monteiro, Luiz Paulo (2017)
This investigation intends to expose aspects related to training for the labor world of the young people who graduated from the Santo Agostinho Rural Family House in Quilombo, the first group that graduated in the State of Santa Catarina in 1997 that joined the institution in 1993. Still looking for making an analysis of the educational action of this institution and the repercussions caused by it in the socioeconomic space families of these young people. Initially is done an analysis of the methodology adopted in this research that is, the use of dialectical materialism, in which capital and labor are not separated but joined dialectically in capitalist production in the perspective of the formation of young people. Later, a historical retrospective of the educational institutions that use the Pedagogy of Alternation within their formation, from Europe to the reasons of the implantation in Brazil, and their differences, is carried out. The second chapter deals with the history of the formation of the Santo Agostinho Rural Family House in Quilombo, that is, it registers an analysis of the study space of the young graduates and also a brief understanding of the methodology and instruments of the Alternation Pedagogy of the agents involved, Young people, families (association) and partners. Also, the role of the monitor in the training process of the young people and their families is emphasized; And also some reflections on the Pedagogy of Alternation in the context of Field Education. The third chapter, on the other hand, deals with the analysis of the socioeconomic situation of the young graduates of CFR Santo Agostinho after almost two decades. At the same time, it makes a redemption of the training received in the perspective of an approximation between work and education, in order to see if the work was conceived as an educational principle, as was the preparation of these young people for the world of work, in a dialectical relation. In the end, there is the analysis of the results, with the presentation of graphs related to the research, analyzing the socioeconomic situation of the family, as well as concrete and historical data, based on interviews and documentary analysis of the Santo Agostinho Rural Family House.